2022
DOI: 10.3390/min12020261
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Recovering Zinc from Electric Arc Furnace Dust by Vacuum Carbothermic Reduction at 20 Pa

Abstract: Electric arc furnace dust (EAFD) presents a contamination hazard due to its heavy metal leachability. The traditional disposal methods of landfill or stacking not only pose a threat to the environment but also waste metal resources. This paper adopted vacuum carbothermic reduction to dispose of EAFD and the zinc metal could be obtained as a product. The reduction ratios of the EAFD were carried out under various reaction temperatures and times at 20 Pa. Furthermore, the kinetics of the reduction process was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The electric arc furnace (EAF) method is estimated to account for about 33% of total steel production [12,13,20]. According to estimates, an EAF produces 10-20 kg of dust for every ton of steel made from iron wastes [14,15,[21][22][23][24]. Every year, the world produces around 7.5 million tons of EAFD, only 45% of which is recycled [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The electric arc furnace (EAF) method is estimated to account for about 33% of total steel production [12,13,20]. According to estimates, an EAF produces 10-20 kg of dust for every ton of steel made from iron wastes [14,15,[21][22][23][24]. Every year, the world produces around 7.5 million tons of EAFD, only 45% of which is recycled [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The authors indicated that the YPFD vacuum processing technology is highly effective and environmentally friendly. The problem of processing EAFD zinc-containing electrosteel process waste is presented in [ 33 ]. The authors focused on determining the activation energy of the reduction process at different temperatures and at a pressure of 20 Pa.…”
Section: Introductionmentioning
confidence: 99%